UNIDADE DEMONSTRATIVA DE COMPOSTAGEM - ALVES, Jonilda da Silva,; MORAIS, Glaucia Almeida,; LIMA, José Vitor Nobrega de,; FREITAS, Letícia da Silva,; CAETANO, Luan Otávio Fernandes,; SILVA, Vitória Aires, (ANAIS DO ENIC, 2023)
-